The Effect of pH and Concentration of KNO3 Solution to the Performance of Nd3+ Ion Selective Electrode Using HPMBP Ionophore - Sosidi, Husain; Buchari, Buchari; Noviandri, Indra (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2018)
The phenyl-3-methyl-4-benzoyl-5-pyrazolone (HPMBP) synthesized and characterized as ionophore in potentiometric analysis of ion selective electrode method (ISE) with polytetrafluoroethylene (PTFE) as the supporting phase. The pH and concentration of the ionic strength adjuster (ISA) were varied to know at the optimum pH and concentration of the ion-selective electrode (ESI) KNO3, thus potential Nd3+ gives the best performance. Before use the PTFE membrane was immersed in a chloroform-HPMBP solution of 1.5-2.0% w/v for 24 h. The pH variation of the buffer solution was adjusted to the pH range of 2-10 using HCl and NaOH solutions, whereas the concentration of KNO3 varies from 10-1 to 10-3 M. The concentration range of Nd3+ is between 10-2 and 10-7 M. The electrode potential measurement results (ENd) obtained the best performance value at pH 4 with KNO3 concentration of 10-2 M, sensitivity (S) 18.39 ± 1.2 mV/decade and response time less than 23 s.